VRK2 gene expression in schizophrenia, bipolar disorder and healthy controls. (August 2016) - Tesli, Martin; Wirgenes, Katrine Verena; Hughes, Timothy; Bettella, Francesco; Athanasiu, Lavinia; Hoseth, Eva S.; Nerhus, Mari; Lagerberg, Trine V.; Steen, Nils E.; Agartz, Ingrid; Melle, Ingrid; Dieset, Ingrid; et al.
Abstract : Background: Common variants in the Vaccinia-related kinase 2 ( VRK2 ) gene have been associated with schizophrenia, but the relevance of its encoded protein VRK2 in the disorder remains unclear. Aims: To identify potential differences in VRK2 gene expression levels between schizophrenia, bipolar disorder, psychosis not otherwise specified (PNOS) and healthy controls. Method: VRK2 mRNA level was measured in whole blood in 652 individuals (schizophrenia, n = 201; bipolar disorder, n = 167; PNOS, n = 61; healthy controls, n = 223), and compared across diagnostic categories and subcategories. Additionally, we analysed for association between 1566 VRK2 single nucleotide polymorphisms and mRNA levels. Results: We found lower VRK2 mRNA levels in schizophrenia compared with healthy controls ( P <10 –12 ), bipolar disorder ( P <10 –12 ) and PNOS ( P = 0.0011), and lower levels in PNOS than in healthy controls ( P = 0.0042) and bipolar disorder ( P = 0.00026). Expression quantitative trait loci in close proximity to the transcription start site of the short isoforms of the VRK2 gene were identified. Conclusions: Altered VRK2 gene expression seems specific for schizophrenia and PNOS, which is in accordance with findings from genome-wide association studies. These results suggest that reduced VRK2 mRNA levels are involved in the underlying mechanisms in schizophrenia spectrum disorders.